Synthesis of Water-Soluble Prodrug of Florfenicol - Qin, G.C.; Chen, L.X.; Yang, P.; Zuo, H.; Li, Z.B. (Asian Journal of Chemistry, 2011)
Water-soluble prodrug of florfenicol was synthesized by introducing a water-soluble small moiety to the hydroxyl of florfenicol according to the prodrug design principles. The water-solubility of the prodrug was about 500 times higher than florfenicol and the water soluble prodrug of forfenicol displays high aqueous solubility and is stable in water as well as in organic solvents.